THE READINESS TO ACCOMMODATE TO ASEAN ECONOMIC COMMUNITY OF HOTELS AND RESORTS IN PRACHUAP KHIRIKHAN PROVINCE - Nathaporn Rojsanyakul, ณัฐธภรณ์ โรจน์สัญญากุล (Dusit Thani College Journal, 2018)
This research was determined to 1) study strategies to support change by external factors 2) to compare the level of preparation for entry into the ASEAN Economic Community and 3) study the relationship between strategies to support the change of external factors to prepare for entry into the ASEAN Economic Community. The samples are hotels and resorts in Prachap Khirikhan Province comprising of 99 3 star hotels, 43 4 star hotels and 16 5 star hotels totaling 158 hotels. Data were collected from management or representatives responsible for the marketing and sales of hotels and resorts. Questionnaires were used to collect data. The statistics used in this study include frequency, mean and standard deviation, independent t-test, One-way ANOVA and Pearson’s Product Moment Correlation. Findings were as follows: 1) Hotels and Resorts in Prachap Khirikhan province with 3-5 stars; most participants are members of the Thai Hotel Association and commented that the ASEAN Economic Community is an opportunity for the tourism industry rather than being a barrier. 2) Hotels and resorts in Prachap Khirikhan Province have strategies to adapt to changing external factors as a whole, at a high level. The primary strategy is the overall business strategy, followed by marketing, finance, and production /services, technology or innovation and human resources. 3) Hotels and resorts in Prachap Khirikhan province are preparing to enter the ASEAN Economic Community as a whole, was shown as moderate. The highest level of preparation was shown as network, followed by products and services, management, innovation and information technology, growth abroad, personnel, retaining existing customers and expanding their your customer base.